Pengaruh Model Inquiry Learning terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPA di MTs Nurul Barkah Baturaja Betung Pematang Sawa - Ardiyanto, Slamet; Saroh, Sitimay; Umoratun, Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study employs the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consists of four main stages: planning, action implementation, observation, and reflection. The research was conducted in two cycles to analyze the impact of the Inquiry Learning model on students’ critical thinking skills in science subjects at MTs Nurul Barkah Baturaja Betung Pematang Sawa. The research subjects were 30 eighth-grade students. Data collection was carried out through written tests (pre-test and post-test), observations, and interviews. The tests were used to measure the improvement of critical thinking skills based on indicators such as analyzing, evaluating, and drawing conclusions. Observations were conducted to assess student engagement in the learning process, while interviews were used to understand students’ and teachers’ responses to the implementation of Inquiry Learning. The collected data were analyzed using both quantitative and qualitative techniques. Quantitative analysis was performed by comparing pre-test and post-test scores using a t-test to determine the significance of improvements in critical thinking skills. Qualitative analysis was conducted descriptively on the results of observations and interviews to explore factors influencing the effectiveness of Inquiry Learning-based instruction. The results of this study are expected to show an improvement in students’ critical thinking skills after the implementation of the Inquiry Learning model. If the first cycle’s outcomes are not optimal, the second cycle will be conducted with improvements to the learning strategies. Thus, this research can provide recommendations for teachers in implementing Inquiry Learning as an effective method to enhance students’ critical thinking skills in science subjects.